The Influence of Mentoring on Career Development of University Tutors: A Narrative Review - Chinegbonkpa Hope Nwakanma (Didaktika: Jurnal Kependidikan, 2024)
Mentoring has long been recognized as a tool for professional development, particularly for university tutors. This research aims to examine the influence of mentoring on the career development of university tutors by emphasizing the benefits of mentoring relationships and their impacts on tutors' professional growth. The article presents a narrative analysis of the existing literature on tutor mentoring and career development. The findings demonstrate that mentoring programs have a significant impact on the career development of university tutors, as they provide guidance, support, and opportunities for personal and professional growth. Moreover, mentoring helps tutors develop crucial skills such as effective communication, leadership, and research abilities. It also contributes to increased job satisfaction, retention rates, and teaching quality at their respective institutions. The author recommends establishing structured and well-supported mentoring programs to maximize the positive impact on the career progression of university tutors.